PENGARUH PEMBERIAN PUPUK BOKASI FESES KUDA SANDLEWOOD TERHADAP PRODUKTIVITAS INDIGOFERA ZOLLINGERIANA - Zeverian Mendonza Umbu Kaborang; Marselinus Hambakodu (JURNAL PETERNAKAN SABANA, 2022)
The purpose of this study was to determine the effect of applying sandelwood horse feces bokashi fertilizer on the productivity of Indigofera zollingeriana. This study used a completely randomized design (CRD) with 5 treatments and 4 replications consisting of: P0=Without sandlewood horse feces bokashi fertilizer/planting hole, P1=200 gram/planting hole, P2=500 gram/planting hole, P3=800 gram/ planting hole, and P4=1000gram/planting hole.The variables observed in this study consisted of plant height, number of leaves, stem diameter, fresh material production, and dry matter production. The results showed that the application of bokashi fertilizer from manure/horse feces had a significant effect (P<0.05) on plant height, number of leaves, stem diameter, fresh material production and dry matter production. Conclusion, giving of sandlewood horse bokashi fertilizer at level 1000 gram/planting hole can increase plant height, stem diameter, fresh material production, and Indigofera zollingeriana dry matter production.